Multipath Routing as a Tool for Energy Saving in Transport Software Defined Network - Yevsieieva, O.; Ilyashenko, Ye. (KHARKIV NATIONAL UNIVERSITY OF RADIO ELECTRONICS, 2015)
The most important features of software defined networks are related to resource virtualization and centralized optimal control that is fully programmatically realized. In turn it gives rise to development of mathematical model which allows to find the optimal solution. On the other hand important role in optimization process belongs to criterion of optimality (objective function). Taking into account global world trends the paper offers mathematical model of SDN-driven transport packet optical network that allows to optimize network resources according to energy saving criterion. It will be shown that multipath routing over virtualized IP-links leads to saving 10% of power consumption per every additionally used path.
Keywords: Telecommunications; transport software defined network; multipath routing; mathematical model; energy saving